2016
DOI: 10.1111/ejn.13166
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic progesterone Norgestrel is neuroprotective in stressed photoreceptor‐like cells and retinal explants, mediating its effects via basic fibroblast growth factor, protein kinase A and glycogen synthase kinase 3β signalling

Abstract: The synthetic progesterone Norgestrel has been shown to have proven neuroprotective efficacy in two distinct models of retinitis pigmentosa: the rd10/rd10 (B6.CXBI-Pde6b(rd10)/J) mouse model and the Balb/c light-damage model. However, the cellular mechanism underlying this neuroprotection is still largely unknown. Therefore, this study aimed to examine the downstream signalling pathways associated with Norgestrel both in vitro and ex vivo. In this work, we identify the potential of Norgestrel to rescue stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 65 publications
(95 reference statements)
1
38
0
Order By: Relevance
“…Previously shown to protect through an upregulation of growth factors [12, 13], this study highlights a novel role for Norgestrel, in acting directly upon microglial cells to dampen damaging inflammatory processes. This is an important finding as recent literature has shown that microglial cells may potentiate retinal disease [18, 19, 21, 44, 63, 64].…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Previously shown to protect through an upregulation of growth factors [12, 13], this study highlights a novel role for Norgestrel, in acting directly upon microglial cells to dampen damaging inflammatory processes. This is an important finding as recent literature has shown that microglial cells may potentiate retinal disease [18, 19, 21, 44, 63, 64].…”
Section: Discussionmentioning
confidence: 58%
“…Due to the difficulty in isolating pure photoreceptor primary cultures and in order to assess the interaction between microglia and photoreceptors, we utilized the cone photoreceptor-like 661W cell line. Our group has previously used 661Ws as an in vitro model to study how photoreceptors respond to stressful stimuli and to understand how Norgestrel works in providing neuroprotection [1113]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Norgestrel is a progesterone analogue that acts through progesterone receptors to elicit its downstream effects (Ruiz Lopez et al, ; Wyse‐Jackson et al, ; Wyse Jackson & Cotter, ; Wyse Jackson, Roche, Byrne, Ruiz‐Lopez, & Cotter, ). The presence of several progesterone receptors in the retina has been established (Wyse Jackson et al, ).…”
Section: Introductionmentioning
confidence: 99%